Intrathoracic Benign Goiter Imaged by 18F-FDG-PET. Issue 32 (August 2015) - Wakahara, Shigeyuki; Konoshita, Tadashi; Sakai, Ai; Nakaya, Takahiro; Ichikawa, Mai; Yamamoto, Katsushi; Imagawa, Michiko; Kimura, Hirohiko; Okazawa, Hidehiko; Ishizuka, Tamotsu; Yiyan, Liu.
<x xml:space="preserve">Abstract</x> Abstract A 55-year-old woman was referred for a suspicion of mediastinal tumor through plain X-ray photography (X-P). Magnetic resonance imaging (MRI) revealed a 3 cm diameter tumor which seemed to connect to the thyroid and projected into the mediastinum. A fine needle aspiration biopsy was tried but could not reach a conclusive diagnosis. Thereby, fluorine-18-fluorodeoxyglucose positron emission tomography (18F-FDG-PET) was performed and a high accumulation was revealed with standardized uptake value (SUV) of 3.8. Thus, the right lobe excision procedure was enforced. The obtained tumor was continuous to the right lobe as expected. Microscopically, the encapsulated tumor consisted of atypical large-sized follicles without malignant characteristics. Thus, histological diagnosis was follicular thyroid adenoma. Thus, follicular adenoma of thyroid could present negative iodine-123-radioisotope (123I-RI) uptake and positive 18F-FDG-PET accumulation.